Business model shifts: masjid kitchens as soup kitchens, jobs employment and empowering asnaf entrepreneurs, and income generation for the masjid - Ahmad Dahlan, Abdul Rahman; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Mohamadali, Noor Azizah; Mahri, Nurhafizah; Abdul Aziz, Normaziah; Ismail, Amelia Ritahani; et al. (2021)
The UNICEF report titled “Families on The Edge” dated October 2020, stated that COVID-19 crisis has pushed more low-income or poor B40 urban Malaysian families into poverty. The poverty rate of these B40 urban families in 2020 is higher than last year, with 50% of the families now living in absolute poverty. 70% of these households reported that COVID-19 had affected their ability to meet their basic living expenses. 37% reporting that they struggle to purchase enough food for their families, while 35% are unable to pay their bills on time. This paper adapted the Design Thinking (DT) methodology. This is to understand and define the key B40 urban families problems; ideation of possible solution options, validation of solution options by various customer segments; and to suggest a conceptual business model as possible solution. This includes conducting literature review and benchmarking, and conducting interviews. An initial business model using Business Model Canvas (BMC) framework was formulated; tested and validated by various customer segments. Hence, the main contribution of this paper is to offer a validated conceptual business model in transforming current masjid kitchen (or mKitchen) as a potential in (a) providing soup kitchen for the poor B40 and Asnaf community, (b) providing job employment while reskilling, empowering, and nurturing the Asnaf as food entrepreneurs, and (c) generating income for the masjid via rental of existing kitchen facilities. This is to turn the Asnaf community ‘Dari Penerima Zakat ke Pembayar Zakat’ or from Zakat receivers to Zakat contributors. The conceptual mKitchen business model can be adopted or adapted for possible implementation, in general, by masjid or mosques.